Perlindungan Hukum Terhadap Hak Anak Angkat Berdasarkan Hukum Positif Di Indonesia - Wahyudi; Ahmad Syarifudin Juang; Usep Saepullah; Muhammad Husni Abdulah Pakarti (Yayasan Cendekia Gagayunan Indonesia, 2024)
This research was conducted with the aim of knowing the rights of adopted children and the protection of their rights in Indonesia. Child protection concerning various aspects of life and livelihood has been regulated in laws and regulations. In the practice of adopting children in Indonesia, there are still various ways, namely the adoption of children in a customary manner that adheres to Islamic teachings and legally through an application to the court. In fact, there are still many adoptions of children in a traditional manner so that the protection of their rights is not guaranteed. The method used in this study uses a normative juridical research method where legislation, books, journals and other sources that are considered relevant to the problem to be studied become the basis for research, and descriptive analysis is carried out by describing the facts. existing facts with normative juridical legal materials. The results obtained in this study indicate that the position of an adopted child in Islam does not sever the blood relationship between an adopted child and his biological parents, in contrast to civil law an adopted child is sever his relationship with his biological parents, in customary law the position of an adopted child depends on the jurisdiction, because some traditional areas in Indonesia differ in determining the position of adopted children. The protection of adopted children has the same position as children in general with the following protections, protection in the field of religion, protection in the field of education, protection in the health sector, protection in the social sector.